2020
DOI: 10.1111/bjet.13048
|View full text |Cite
|
Sign up to set email alerts
|

Learning by explaining to oneself and a peer enhances learners’ theta and alpha oscillations while watching video lectures

Abstract: In the present study, we tested the effectiveness of three learning strategies (self‐explanation, learning by teaching and passive viewing) used by students who were learning from video lectures. Effectiveness was measured not only with traditional measures, but also with electroencephalography (EEG). Using a within‐subjects design, 26 university students viewed three sets of short lectures, each presenting a different set of English vocabulary words and were asked to use a different learning strategy for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 66 publications
0
56
2
Order By: Relevance
“…Neural oscillations in the alpha band are related to an increase in internal attention-demanding cognitive processing ( Klimesch, 2012 ; Fink and Benedek, 2014 ). Our study suggests that the color-coded group had a greater engagement of working memory and attention than the grayscale group, allowing information to be processed at a deeper level and thus resulting in better learning performance ( Pi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Neural oscillations in the alpha band are related to an increase in internal attention-demanding cognitive processing ( Klimesch, 2012 ; Fink and Benedek, 2014 ). Our study suggests that the color-coded group had a greater engagement of working memory and attention than the grayscale group, allowing information to be processed at a deeper level and thus resulting in better learning performance ( Pi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
“…The theta band is related to the working memory. The increases in theta oscillations are related to high working memory activity as well as successful memory encoding ( Miller et al, 2018 ) and retrieval ( Solomon et al, 2019 ; Pi et al, 2021 ). Therefore, deep processing of learning material in working memory can successfully encode memory ( Khader et al, 2010 ; Lin et al, 2017 ), and working memory maintenance can forecast long-term memory ( Hsieh and Ranganath, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research has shown that the learning-by-teaching effect also replicates in non-interactive settings (e.g., Fiorella & Mayer, 2013;Hoogerheide et al, 2014;Pi et al, 2021;Rittle-Johnson et al, 2008). Learning by non-interactive teaching entails studying learning materials and then teaching the material to an actual, remote, or imaginary audience, and lacks interaction with other students.…”
Section: What Is Learning By (Non-interactive) Teaching?mentioning
confidence: 99%
“…Any such examinations should preferably include (multiple) process measures. Recent studies did start to include process measures, such as arousal (Hoogerheide et al, 2019a;Pi et al, 2021), motivation (Hoogerheide, et al, 2019b;Jacob et al, 2021), or adaption processes Jacob et al, 2020a;Lachner et al, 2020). However, most studies only included a single process measure, making it difficult to compare the relative relevance and the interplay of different mechanisms.…”
Section: Research Agenda 1: Mechanisms Of Non-interactive Teachingmentioning
confidence: 99%